Synthesis, biochemical, and biological evaluation of C2 linkage derivatives of amino sugars, inhibitors of glucokinase from Trypanosoma cruzi. (1st September 2021) - Green, Scott B.; Lanier, Robert J.; Carey, Shane M.; Morgan, David R.; Gracz, Hanna; Sherman, Julian; Rodriguez, Ana; D'Antonio, Edward L.
Graphical abstract: Highlights: Novel amino sugar analogues were synthesized and purified in a one-step method. Eighteen amino sugar analogues having either a d -GlcN, d -ManN, or d -GalN scaffold were screened against Tc GlcK and a T. cruzi parasite infection of mammalian cells. Tc GlcK was notably inhibited by amino sugar analogues having the d -GlcN scaffold. Abstract: Eighteen amino sugar analogues were screened against Trypanosoma cruzi glucokinase ( Tc GlcK), a potential drug-target of the protozoan parasite in order to assess for viable enzyme inhibition. The analogues were divided into three amino sugar scaffolds that included d -glucosamine (d -GlcN), d -mannosamine (d -ManN), and d -galactosamine (d -GalN); moreover, all but one of these compounds were novel. Tc GlcK is an important metabolic enzyme that has a role in producing G6P for glycolysis and the pentose phosphate pathway (PPP). The inhibition of these pathways via glucose kinases (i.e., glucokinase and hexokinase) appears to be a strategic approach for drug discovery. Glucose kinases phosphorylate d -glucose with co-substrate ATP to yield G6P and the formed G6P enters both pathways for catabolism. The compound screen revealed five on-target confirmed inhibitors that were all from the d -GlcN series, such as compounds 1, 2, 4, 5, and 6 . Four of these compounds were strong Tc GlcK inhibitors (1, 2, 4, and 6 ) since they were found to have micromolar inhibitory constant (Ki ) values around 20 μM. Three of the on-target confirmed inhibitors (1, 5, and 6 ) revealed notable in vitro anti- T. cruzi activity with IC50 values being less than 50 μM. Compound 1 was benzoyl glucosamine (BENZ-GlcN), a known Tc GlcK inhibitor that was the starting point for the design of the compounds in this study; in addition, Tc GlcK – compound 1 inhibition properties were previously determined [D'Antonio, E. L. et al. (2015) Mol. Biochem. Parasitol. 204, 64–76]. As such, compounds 5 and 6 were further evaluated biochemically, where formal Ki values were determined as well as their mode of Tc GlcK inhibition. The Ki values determined for compounds 5 and 6 were 107 ± 4 μM and 15.2 ± 3.3 μM, respectively, and both of these compounds exhibited the competitive inhibition mode.